Research on the Comparison of Investment Markets for Chinese and German Traditional Vehicle Enterprises and Development Strategies for German Enterprises under the New ESG Landscape - Xie, Qirui (Transactions on Economics, Business and Management Research, 2024)
The automotive industry is undergoing a significant transformation due to the emergence of new power vehicles (NEVs) and the integration of environmental, social, and governance (ESG) considerations. This research conducts a comparative analysis of the NEV and ESG landscapes in China and Germany, two major players in the global automotive market. The analysis reveals similarities and differences between the two countries in terms of market size, regulatory environment, customer preferences, and automaker strategies. Key findings underscore the importance of comparability and standardization in ESG and NEV performance, the impact of trade tensions and protectionism, and the potential negative consequences associated with ESG and NEV practices. To address these challenges, the study recommends the establishment of uniform guidelines and standards, enhanced collaboration and partnerships among stakeholders, and the implementation of holistic policymaking approaches. These insights are valuable for automakers, policymakers, and investors in navigating the complexities of sustainability-driven changes in the automotive industry. Moreover, they contribute to the broader discourse on responsible finance and investing. The findings and recommendations presented in this research can inform future research endeavors and industry practices, facilitating the accelerated adoption and diffusion of NEV and ESG technologies and practices on a global scale.